Learning Al-Islam and Kemuhammadiyahan by Using Blended Learning in the New Normal at MTs Muhammadiyah Lubuk Jambi - Tarsupon Tarsupon (Ruhama : Islamic Education Journal, 2021)
The implementation of learning in the new normal is not much different from learning during the Covid-19 pandemic, therefore it takes teacher creativity for successful learning implementation. The creativity of Al-Islam and Kemuhammadiyahan teachers at MTs Muhammadiyah Lubuk Jambi is to use blended learning, therefore this research aims to reveal how the implementation of blended learning in AIK learning in the new normal. The study uses a qualitative approach, the data source consists of key informants and additional informants. Data collection techniques are observation, interviews and documentation studies. Data is analyzed using interactive techniques. The application of blended learning model in MTs Muhammadiyah Lubuk Jambi is done by combining online and offline.  The obstacles faced by using blended learning are from the aspect of teachers, learners and facilities. Research recommendations require comprehensive training to realize teachers who have information technology capabilities.